Potential of Trichoderma SP as a Control of Phytopthora Palmivora Causes Leaf Blight of Cocoa Seeds - M. Juli Nurudin; Sutarman Sutarman (Nabatia, 2014)
In nature, "soil-borne" Trichodermacommonly as endophytic and survive on the surface of leaf. However, study and analysis related to controlling "water -borne" pathogens on the leaf surface is relatively seldom. Aims of this study were to describe the selected isolates ofTrichoderma sp. From cocoa planting soiland determine its inhibitory effect of Phytophthora palmivora by in vitro. The experiment was conducted at the Laboratory of Microbiology, Faculty of Agriculture UMSIDA on January-March 2014. This research consist of: (i) exploration of isolatedTrichoderma sp. From cocoa plantation in Klepu, District Sumbermanjing, Malang (East Java) which includes to describing and calculating the viability of conidiospore and (ii) antagonist analysis ofTrichoderma sp. against P. palmivoraby in vitro. The isolates of Trichoderma sp. TcN-Klp with green color colonies had 100 % germination rate after 11hoursrelative incubation period and inhibits the growth of P. palmivora by in vitro on PDA up to 47.06 % at 4 days after inoculation.